House Season 8 Disc 4 Season eight. Disc four. - Laurie, Hugh, 1959-; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2012)
House is serving a prison sentence for driving his car into Cuddy's living room, and when his sentence ends early, he finds the Diagnostic Medicine Department has gone through a transition in his absence and he must deal with a new chain of command and personnel changes to his team.
Gut check -- We need the eggs -- Body and soul -- The c-word -- Post mortem.
Originally broadcast as single episodes of the 2011-2012 television program.
Title from disc label.
Hugh Laurie.
Rating: Not rated.
DVD, region 1, anamorphic widescreen (1.78:1) presentation; Dolby digital 5.1; dual-layer.
English dialogue, Spanish subtitles; subtitled for the deaf and hard of hearing.
Keywords: Physician and patient -- New Jersey -- Plainsboro -- Drama; Hospitals -- Medical staff -- New Jersey -- Plainsboro -- Drama; Hospital patients -- New Jersey -- Plainsboro -- Drama; New Jersey -- Plainsboro; Drama; Medical television programs; Television series; Video recordings for the hearing impaired